EGFR and KRAS mutations in pulmonary pleomorphic carcinoma and their correlation with clinicopathologic features - Jia, Xiaoli; Chen, Gang (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Pulmonary pleomorphic carcinoma (PPC) of the lung is a subset of poorly differentiated non-small cell lung cancers (NSCLCs). Because of its rarity, information on epidermal growth factor receptor (EGFR) and Kirsten rat sarcoma viral oncogene (KRAS) mutations is controversial and sparse. The aim was to investigate the two key oncogenes’ characteristics and their correlation with clinical variables. Material and methods : We retrospectively screened 110 paraffin-embedded surgically resected specimens from patients with PPC. Of these, follow-up information was available for 48 patients. We then successfully analyzed 70 PPC samples and examined EGFR and KRAS mutation status by direct sequencing. The findings were correlated with a control group of patients with other NSCLCs. Results : In our department, PPC comprised about 1.57% of surgical resected cases (110/6990). 37.4% of patients smoked. EGFR mutations were detected in 11 cases (15.7%), with a significantly higher frequency in women than men (p = 0.011). KRAS mutations were detected in 10 cases (14.3%) and were more often found at age 65 or older (p = 0.02). Of interest, in PPC, all KRAS mutations occurred in never smokers. Also, most never smokers have transversion mutations (G→T) in PPCs and other NSCLCs. Conclusions : Our results demonstrated a similar EGFR and KRAS mutation rate in Chinese PPC patients. EGFR tyrosine kinase inhibitors may be a treatment option for PPCs with EGFR mutations. Of note, EGFR mutations in PPC were commonly identified in women; therefore women should be high-priority candidates for mutation screening.